A new design of square paralelipedic treatment chamber for food processing using pulsed electric field - Bellebna, Yassine; Ramdani, Nadia; Khalfi, Yassine; Tilmatine, Amar (جامعة الوادي - university of el oued, 2021)
Today, the influence of pulsed electric field is one of the key components in the PEF treatment process. The manuscript focused on the design and development of new multiple square paralelipedic PEF treatment chamber (TC2) which houses several electrodes, and testing the efficacy of this chamber on beet juice extraction compared with a single square paralelipedic treatment chamber (TC1) which houses only two electrodes. The aim of this paper to mention the effect of the Electric Field distribution based on Response Surface Modeling (RSM) for identifying the set point of the juice extraction process using pulsed electric field pre-treatment using a laboratory experimental bench. Obtained results show that the TC2 of PEF treatment has significant effect not only in juice yield, but also for enhancement of the betanin concentration and saving in consumed energy
Article
Keywords: Treatment chamber; Pulsed electrical field (PEF); RSM technique; Absorbance; Beet juice.